Effects of Selected Food Additives on the Gut Microbiome and Metabolic Dysfunction-Associated Steatotic Liver Disease (MASLD) - Sara Jarmakiewicz-Czaja; Aneta Sokal-Dembowska; Rafał Filip (Medicina)
The purpose of this article is to present selected food additives as disruptors of normal intestinal homeostasis with a potential impact on the development of metabolic dysfunction-associated steatotic liver disease (MASLD). A comprehensive literature search was conducted in three major electronic databases: PubMed, ScienceDirect, and Google Scholar. MASLD is a prevalent liver condition that is closely related to the global rise in obesity. Its pathogenesis is multifactorial, with genetic, environmental, and metabolic factors playing a key role. The “multiple-hit” hypothesis suggests that a Western-style diet, rich in ultra-processed foods, saturated fats, and food additives, combined with low physical activity, contributes to obesity, which promotes lipid accumulation in the liver. Recent studies underscore the role of impaired intestinal homeostasis in the development of MASLD. Food additives, including preservatives, emulsifiers, and sweeteners, affect gut health and liver function. Selected preservatives inhibit pathogenic microorganisms but disrupt the intestinal microbiota, leading to changes in intestinal permeability and liver dysfunction. Some emulsifiers and thickeners can cause inflammation and alter the gut microbiome, contributing to liver steatosis. Furthermore, the use of sweeteners such as sucralose and aspartame has been linked to changes in liver metabolism and intestinal microbial composition, which in turn promotes metabolic disorders.